2012
DOI: 10.1103/physrevb.85.054402
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated magnetic vortices in hexagonal lattice of magnetic nanocaps

Abstract: Magnetic properties of hexagonal lattices of touching magnetic nanocaps fabricated by Co film deposition on a surface of polymethyl methacrylate colloidal crystals was studied as a function of both period (120-450 nm) and thickness (30-60 nm). Magnetization configurations and hysteresis loops of the samples were investigated by magneto-optic Kerr effect and magnetic force microscopy. Formation of frustrated hexagonal lattices of magnetic vortices was found in the system. Magnetic coupling of the nanocaps can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…It has been shown that the ferromagnetic behavior of such a structure is governed by the geometry of the network. [18][19][20][21] However, neither a detailed analysis of the magnetic properties has been done yet, nor has an appropriate model been suggested for this system so far.…”
mentioning
confidence: 99%
“…It has been shown that the ferromagnetic behavior of such a structure is governed by the geometry of the network. [18][19][20][21] However, neither a detailed analysis of the magnetic properties has been done yet, nor has an appropriate model been suggested for this system so far.…”
mentioning
confidence: 99%
“…The coupling strength, however, will strongly depend on the Py thickness. It is expected that this coupling might influence the in-plane circulation orientation of connected caps, leading to frustration in a hexagonal cap array [43,44] or even to the formation of anti-vortices [48,49] at the contact area when the circulations are contra-rotating. Please note that due to the curved particle surface, the thickness of the deposited Py layer in radial direction decreases from the top center of the film cap towards the rim, thus the vortex core area is expected to be enlarged compared to planar vortex structures.…”
Section: Resultsmentioning
confidence: 99%
“…Strong coupling is induced by deposition of thick Py films, where neighboring caps will be interconnected at the contact areas, resulting in direct magnetic exchange coupling. Here, we report on the influence of magnetic coupling on the reversal behavior and the in-plane circulation orientation of neighboring caps, which can lead to frustration in a hexagonal cap array [43,44] or even to unexpected magnetization configurations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far the magneto-optical properties of magnetic films on colloidal crystals have been investigated 6 . Following this initial work there has been interest in geometrical frustration being built into such nanostructures [7][8][9] . In those works the frustration originated from the remanent state vortex on a given dome being unable to satisfy all it's nearest-neighbor interactions with other vortices within the HCP lattice.…”
mentioning
confidence: 99%